2014
DOI: 10.1097/jcp.0b013e3182a6096e
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Antipsychotics in Behavioral Disorders in Elderly People With Dementia

Abstract: In recent years, the use of antipsychotics has been widely debated for reasons concerning their safety in elderly patients affected with dementia. To update the use of antipsychotics in elderly demented people, a MEDLINE search was conducted using the following terms: elderly, conventional and atypical antipsychotics, adverse events, dementia, and behavioral and psychotic symptoms in dementia (BPSD). Owing to the large amounts of studies on antipsychotics, we mostly restricted the field of research to the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 97 publications
1
60
0
4
Order By: Relevance
“…On the one hand, the large degree of unexplained mortality in either situation might demand investigation of other unsuspected adverse events. For instance, drug-drug interactions with antipsychotics may occur in the elderly whose age-related changes in drug metabolism and clearance may be exacerbated by complex medication regimens for comorbid conditions [70]. On the other hand, our inability to explain the mortality difference despite considering many known risks is also consistent with hypotheses of residual and unmeasured differences between patients who receive FGAs versus SGAs.…”
Section: Discussionmentioning
confidence: 59%
“…On the one hand, the large degree of unexplained mortality in either situation might demand investigation of other unsuspected adverse events. For instance, drug-drug interactions with antipsychotics may occur in the elderly whose age-related changes in drug metabolism and clearance may be exacerbated by complex medication regimens for comorbid conditions [70]. On the other hand, our inability to explain the mortality difference despite considering many known risks is also consistent with hypotheses of residual and unmeasured differences between patients who receive FGAs versus SGAs.…”
Section: Discussionmentioning
confidence: 59%
“…The only other known risk factors for QTc prolongation were being elderly and female and, potentially, receiving fluoxetine, which had not shown that effect in this patient previously. 2 Ms A's serum potassium and magnesium levels were both within normal limits. Manual QTc measurements were done with lead V5 using the tangential method with heart rate correction using the Bazett formula.…”
mentioning
confidence: 90%
“…Concurrently, risk for iatrogenic corrected QT (QTc) prolongation on electrocardiogram (ECG) remains a concern with the use of many antipsychotic agents because of its associated potential for fatal arrhythmias. 2 Many elderly patients require antipsychotic pharmacotherapy yet incur risks from inherent cardiac disease, begging the question: How does one treat a psychotic or delirious patient with a prolonged QTc? The following case illustrates experience at our institution with safe reinitiation of aripiprazole after myocardial infarctionrelated QTC prolongation in an older adult with chronic psychosis.…”
mentioning
confidence: 99%
“…En psicogeriatría, estos fármacos se usan siempre en la dosis más baja posible, evaluan-do diariamente su real necesidad, ya que su uso prolongado puede incrementar el riesgo de muerte y de eventos cardiovasculares en pacientes con demencia 17 . Por este motivo, previo al uso de antipsicóticos se recomienda evaluar la presencia de enfermedades cardiovasculares, intervalo QT en el ECG, alteraciones hidroelectrolíticas, antecedente familiar de torsades de pointes y uso concomitante de fármacos que podrían prolongar el QT 18 .…”
Section: Importancia Del Deliriumunclassified